الدليل الوجيز على المراجع والمصادر العربية - Ainul Haq Nawawi (OKARA: Jurnal Bahasa dan Sastra, 2016)
The role of reference in the scientific activities, the dissertation writing, thesis, theses, papers, journals, books, are very urgent, its presence is vital to the perfection and accuracy of writing. Arabic reference is very varied and diverse, either it is from makhtutat (manuscript), ummahat al kutub (the parent reference) in every discipline of the Islamic sciences and Arabic language and literature. Arabic references and literatures are very diverse , in accordance with the various sciences of linguistic studies, for example : the science of al lughah (linguistics), fiqhu al lughah (philology), adab al-lughah (literature), balaghah (the beauty of language), al-mawsoo'ah al lughawiyyah wal adabiyah (encyclopedia of language & literature), and etc . The first study in linguistics starts from the dictionaries and linguistic /philology.